The benefit of halal certificate application from small and medium industries perspective / Nur Sabrina Hashim and Ahmad Rosli Mohd Nor - Hashim, Nur Sabrina; Mohd Nor, Ahmad Rosli (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
This paper aims to identify the benefit of halal certificate from perspective of Malay SME industry. Statistics from 2010 until 2022 on confirmation of Malaysian halal certification application by year based on company status and industry at Kedah show that total halal application of sector small and medium is 627. Of this amount, 408 applications are from non-Bumiputera, while only 219 are from Bumiputera. The percentage of Bumiputera enterprises is relatively tiny in applying for a halal certificate for their business. Due to that, it's necessary to know type of halal application and identify the benefits of halal certification in the industries. This study follows qualitative research and ten employees from Kedah who manage industrial firms were interviewed. According to the study's findings, there are nine (9) application schemes for Malaysian Halal Certification based on Malaysia Halal Certification Procedure Manual (Domestic) which is food and beverage product, cosmetic product, pharmaceutical, good product, food premise, logistic, slaughterhouse, OEM, and medical device. There are three major benefits in Halal certificate which are (1) consumers are confident that the products they eat or use are clean, pure from prohibited substances and includes environmental cleanliness, (2) Halal certification give advantages in marketability and (3) Halal certification could give a competitive edge against competitors who do not apply for halal certification. The implications of this study, it is crucial for JAKIM to create information and awareness programs for Muslim entrepreneurs related benefits and needs to have a halal certificate in Malaysia to line with JAKIM's policy. It's crucial to ensure enforcement and compliance with standards halal among SME in this country and make Halal as a priority to all sectors.